SEMANGAT ADMIRAL CHENG HOO DAN EKSPRESI TOLERANSI MASJID MUHAMMAD CHENG HOO INDONESIA - Freddy H. Istanto (DIMENSI (Journal of Architecture and Built Environment), 2003)
The existence of Cheng Hoo's Indonesian Mosque Architecture in Surabaya is the presentation of Chinese architecture nuance. It is a new revelation for Indonesian mosque architecture. At the same time it is also the resurrection of the treasure of Indonesian architecture which had disappeared for a very long time. It is the architecture which presents itself as a synthesis of various attractive local elements. The building's expression indicates the spirit of tolerance which is the strong character of the Chinese ancestors. Primarily in this case, are the ideal and the cosmopolitan ways of living by Admiral Cheng Hoo who always lived in harmony with the new environment. Abstract in Bahasa Indonesia : Arsitektur Masjid Muhammad Cheng Hoo Indonesia di Surabaya hadir dalam sebuah arsitektur yang bernuansa Tiongkok. Sebuah bentuk arsitektur baru untuk sebuah masjid di Indonesia sekaligus sebuah pemunculan bentuk arsitektur yang telah lama hilang dalam khazanah arsitektur Indonesia. Sebuah wujud yang juga hadir sebagai perpaduan beragam elemen-elemen lokal yang menarik. Ekspresi arsitektur ini merupakan ekspresi semangat toleransi yang selalu mampu beradaptasi dengan lingkungan barunya, seperti sikap hidup nenek moyang etnis Tiongkok. Utamanya teladan dan sikap hidup Admiral Cheng Hoo yang kosmopolitan dan selalu hidup harmoni dengan lingkungan barunya. Kata kunci: arsitektur Tiongkok, arsitektur Muhammad Masjid Cheng Hoo, teladan Admiral Cheng Hoo.